ANALISIS PENGARUH FAKTOR PENYEBAB NON-EXCUSABLE DELAY PADA PROYEK KONSTRUKSI GEDUNG DI MANADO - Stevie Andrean; I Putu Artama Wiguna; Tri Joko Wahyudi (Journal of Civil Engineering, 2018)
Delays are the global phenomena occur in the construction industry. Delays negatively affect project performance. Based on the category which causes delay, this research especially discussing about Non-Excusable Delays, in which contractors holds the responsibility for the delay. The purpose of this study is to analyze the relation between factors, and its effects on delays in Manado. Model development is based on previous research and literature review. Primary data collection was done through distribution of questionnaires to project managers, site managers or implementers of contractors who had or are currently dealing with building construction projects in Manado. Data was analyzed using Partial Least Square. The results reveal that Improper Execution Planning directly and positively influence Construction Project Delay. On the other hand, Improper Execution Planning is influenced by Inefficient Site Management while Inefficient Site Management is significantly influenced by Poor Contractor Competencies